Use of telemedicine in the follow-up of Parkinson’s Disease in elderly populations (Research, Society and Development, 2025)
Telemedicine has increasingly established itself as a strategic tool in the management of chronic and neurodegenerative diseases, such as Parkinson’s Disease (PD), particularly among elderly populations. Population aging, combined with functional limitations and difficulties in accessing specialized healthcare services, poses significant challenges to the continuous follow-up of these patients. This study aimed to analyze the scientific evidence regarding the use of telemedicine in the follow-up of parkinson’s disease in older adults. This is a narrative literature review conducted using the pubmed database, employing the descriptors “Aged,” “Parkinson Disease,” and “Telemedicine.” Full-text articles published within the last five years in english, portuguese, or spanish were included. Initially, 46 studies were identified, of which 25 met the inclusion criteria. The results demonstrated that telemedicine shows efficacy comparable to in-person care, particularly in monitoring motor and non-motor symptoms, therapeutic adjustments, and multidisciplinary support. Strategies such as virtual consultations, telerehabilitation, and remote monitoring showed a positive impact on treatment adherence, motor functionality, and quality of life. However, technological barriers, limited digital access, and resistance to the use of technology remain significant challenges. It is concluded that telemedicine represents a viable and promising alternative for the follow-up of parkinson’s disease in elderly populations, with the need to expand digital inclusion strategies and professional and patient training to ensure effective implementation.